RELATIONSHIP BETWEEN OBESITY, PSA, AND PROSTATE VOLUME IN PATIENTS WITH BPH WITHOUT URINARY RETENTION - Ambeng, Yudi Y; Alif, Sabilal; Soebadi, Doddy M (Indonesian Journal of Urology, 2011)
Objective: To study the relationship between obesity, prostate specific antigen (PSA) level, and prostate volume in patients with benign prostate hyperplasia (BPH) without urinary retention.Material & Method: Twenty two BPH patients without urinary retention were enrolled in this study. Patients were classified into 2 groups based on body mass index (BMI). The first group consisted of 11 patients with obesity (BMI ≥ 27 kg/m2), the second group consisted of 11 non obese patients (BMI <  27 kg/m2). Each patient underwent measurement of PSA, prostate  volume and hematocrit. We performed tests for correlation between all variables in both groups. Results: From correlation testing there was a significant relationship between obesity and PSA. With increasing BMI, a lower PSA level was observed (p< 0,05). There was no significant relationship between prostate volume and hematocrit (p > 0,05).Conclusion: There is a significant negative correlation between obesity and PSA in BPH patients without urinary retention